Specific disruption of the ventral anterior temporo-frontal network reveals key implications for language comprehension and cognition - Evie Kourtidou; Dimitrios Kasselimis; Georgia Angelopoulou; Efstratios Karavasilis; Georgios Velonakis; Nikolaos Kelekis; Ioannis Zalonis; Ioannis Evdokimidis; Constantin Potagas; Michael Petrides (Communications Biology, 2022)
Neuropsychological profiling and clinical DTI of three stroke patients highlight the importance of the ventral language system in normal language comprehension and cognition.